2012
DOI: 10.1038/nmeth.2208
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity Orbitrap mass analysis of intact macromolecular assemblies

Abstract: The analysis of intact protein assemblies in native-like states by mass spectrometry offers a wealth of information on their biochemical and biophysical properties. Here we show that the Orbitrap mass analyzer can be used to measure protein assemblies of molecular weights approaching one megadalton with sensitivity down to the detection of single ions. Minor instrumental modifications enabled the measurement of various protein assemblies with outstanding mass-spectral resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
470
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(484 citation statements)
references
References 23 publications
6
470
1
7
Order By: Relevance
“…The Functional Dimer Interface of bGP-We found that the association of two GP monomers into the functional dimer involves helix 2 (residues 49 -77), the ␤4/␤5 loop (residues 180 -198), the capЈ loop (residues [41][42][43][44][45][46][47][48], and the tower helices (residues 259 -278), as observed for mGP and lGP (Fig. 5, a and b).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The Functional Dimer Interface of bGP-We found that the association of two GP monomers into the functional dimer involves helix 2 (residues 49 -77), the ␤4/␤5 loop (residues 180 -198), the capЈ loop (residues [41][42][43][44][45][46][47][48], and the tower helices (residues 259 -278), as observed for mGP and lGP (Fig. 5, a and b).…”
Section: Resultsmentioning
confidence: 59%
“…Native MS was performed on samples containing bGP (1 mg/ml) and phosphorylated bGP (1 mg/ml) using an Exactive Plus EMR mass spectrometer (Thermo Fisher Scientific), which allows analysis of proteins and complexes in native-like states (41). The proteins were desalted by buffer exchange prior to mass spectrometry analysis.…”
Section: Purification Of Recombinant Bgp From E Coli-extractionmentioning
confidence: 99%
“…The experiments described here were carried out using a quadrupoletime-of-flight (Q-TOF) high-mass type of mass spectrometer that has lower resolution in comparison to the Orbitrap instrument (Thermo) (12). MS conditions were therefore first optimized to achieve highly resolved peaks reflecting the small differences in mass between apo-GroEL (801,312 Da) and its nucleotide-bound states (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the AMP-PNP density shows a well-defined density segment (Fig. 3B), for which the fitted atomic model suggests that it corresponds to the very N-terminal residues (residues [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. These N-terminal 20 residues are absent from all p97 crystal structures but one protomer of the ATPcS-bound IBMPFD mutant A232E, which includes residues 12-20 [10].…”
Section: Conformational Changes Of the N-d1 Segmentmentioning
confidence: 99%